Perspective: Revisiting the Field Dependence of TROSY Sensitivity - Takeuchi, Koh (J Biomol NMR, 2016)
The discovery of the TROSY effect (Pervushin et al. 1997) for reducing transverse relaxation and line sharpening through selecting pathways in which dipole-dipole and CSA Hamiltonians partially cancel each other had a tremendous impact on solution NMR studies of macromolecules. Together with the methyl TROSY (Tugarinov and Kay 2004) it enabled structural and functional studies of significantly larger systems. The optimal field strengths for TROSY have been estimated to be on spectrometers operating around 900 MHz (21.14 T) for the (1)H(N) TROSY (Pervushin et al. 1997) while the aromatic (13)C ((13)C(aro)) TROSY is posited to be optimal at around 600 MHz (14.09 T) (Pervushin 2000; Pervushin et al. 1998b). The initial rational was based on the consideration of where the quadratic B(0) field dependences of the TROSY relaxation rates reach a minimum. For sensitivity consideration, however, it is interesting to estimate which field strengths yield the tallest peaks. Recent studies of (15)N-detected TROSYs suggested that maximal peak heights are expected at 1.15 GHz (27.01 T) although the slowest relaxation rates or longest transverse relaxation times T(2) are indeed expected around 900 MHz (21.14 T) (Takeuchi et al. 2016; Takeuchi et al. 2015). This was based on the fact that the heights of Lorentzian lines are proportional to B(o)(3/2) * T(2) (B(o)). Thus, multiplying the parabolic T(2)(B(o)) dependence with the increasing function of B(o)(3/2) shifts the maxima of peak-height field dependence from the T(2) maximum at 900 MHz to higher fields. Moreover, besides shifting the peak height maximum for (15)N TROSY, this analysis yields estimates for optimal peak heights for (1)H(N) detected TROSY to 1.5 GHz, and to 900 MHz for (13)C-detected (13)C(aro)TROSY as is detailed below. To our knowledge, this aspect of field dependence of TROSY sensitivity has not been in the attention of the NMR community but may affect perspectives of NMR at ultra-high fields.